2004
DOI: 10.1007/s00228-004-0841-1
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacokinetic study comparing single and repeated oral doses of 20�mg and 40�mg omeprazole and its two optical isomers, S-omeprazole (esomeprazole) and R-omeprazole, in healthy subjects

Abstract: Treatment with S-omeprazole (esomeprazole; 20 mg and 40 mg) resulted in higher AUC values than with either R-omeprazole or racemic omeprazole after both single and repeated doses due to a lower metabolic rate of S-omeprazole than R-omeprazole and, consequently, racemic omeprazole. S-Omeprazole, R-omeprazole and the racemate were well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
75
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 11 publications
4
75
0
1
Order By: Relevance
“…CYP2C19 and CYP3A4 are associated with the metabolism of esomeprazole in people, and CYP1A1/2 and CYP2D15 are associated in dogs 3, 24. Repeated PO administration of esomeprazole has been shown in human studies to result in an increase in its plasma concentration because of the inhibition of CYP2C19 3.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CYP2C19 and CYP3A4 are associated with the metabolism of esomeprazole in people, and CYP1A1/2 and CYP2D15 are associated in dogs 3, 24. Repeated PO administration of esomeprazole has been shown in human studies to result in an increase in its plasma concentration because of the inhibition of CYP2C19 3.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated PO administration of esomeprazole has been shown in human studies to result in an increase in its plasma concentration because of the inhibition of CYP2C19 3. One study reported that the AUC of repeated PO doses was 2.4‐fold higher than that of a single 40 mg PO dose,3 suggesting that an accumulation of esomeprazole is expected to occur after repeated oral dosing. However, in this current study, the PK properties of esomeprazole in Beagles were slightly different from those observed in human studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations